High level of sporulation of Metarhizium anisopliae in a medium containing by-products - Dorta, Blas (1990)
Solid-state fermentation of rice bran or rice-bran-husk mixtures byMetarhizium anisopliae proved to be highly successful in spore yield. Optimum sporulation response on bran medium occurred when the initial water activity values ranged from 0.982 to 0.999. When bran was supplemented with 50% rice husk, the spore yield almost doubled, but a narrower initial water activity range (0.997–0.999) was optimum. Under these conditions, spore yields were 5–15 times higher (depending on the strain) than those currently obtained on the basis of rice grain fermentations.